Impact of leading line composition on visual cognition: An eye-tracking study - Hsien-Chih Chuang; Han-Yi Tseng; Chia-Yun Chiang (Journal of Eye Movement Research)
Leading lines, a fundamental composition technique in photography, are crucial to guiding the viewer’s visual attention. Leading line composition is an effective visual strategy for influencing viewers’ cognitive processes. However, in-depth research on the impact of leading line composition on cognitive psychology is lacking. This study investigated the cognitive effects of leading line composition on perception and behavior. The eye movement behaviors of 34 participants while they viewed photographic works with leading lines were monitored through eye-tracking experiments. Additionally, subjective assessments were conducted to collect the participants’ perceptions of the images in terms of aesthetics, complexity, and directional sense. The results revealed that leading lines significantly influenced the participants’ attention to key elements of the work, particularly when prominent subject elements were present. This led to greater engagement, longer viewing times, and enhanced ratings on aesthetics and directional sense. These findings suggest that skilled photographers can employ leading lines to guide the viewer’s gaze and create visually compelling and aesthetically pleasing works. This research offers specific compositional strategies for photography applications and underscores the importance of leading lines and subject elements in enhancing visual impact and artistic expression.